(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The world contains an extraordinary variety of ecosystems, ranging from equatorial forests to deserts and including a multitude of different vegetation types. Diversity of biomass and structure is matched by a large variation in productivity. We have some knowledge regarding the productive capacity of these ecosystems, but this knowledge is incomplete and contains a large degree of error.